Terahertz Transmission Characteristics of Free-Standing Fractal Jesus-Cross Structure - Xiong, Ri-Hui; Li, Jiu-sheng (Frontiers in Physics, 2020)
We have fabricated a Jesus-cross structure on aluminum foil using the femtosecond laser technique. Using the terahertz time-domain spectroscopy (THz-TDS) system, the transmission properties of free-standing double-layer crossing fractal structure are tested. The parameters of the proposed structure were optimized using the finite element frequency domain technology of commercial software CST Microwave Studio package. The dimensions of the aluminum foil periodically patterned with crossing fractal structure are 1.5 × 1.5 cm2. The resonant frequencies of the proposed structure are 0.216 and 0.735 THz with 3-dB bandwidths of 62 and 15 GHz, respectively. The transmission ratio can reach to 0.89 and 0.57. It indicates the structure having dual-band filtering performance. This work has the potential to open a new avenue as a filter working for free-space terahertz radiation.